A Hierarchical Z‑Scheme α‐Fe2O3/g‐C3N4 Hybrid for Enhanced Photocatalytic CO2 Reduction. Issue 10 (19th January 2018) - Jiang, Zhifeng; Wan, Weiming; Li, Huaming; Yuan, Shouqi; Zhao, Huijun; Wong, Po Keung
Abstract: The challenge in the artificial photosynthesis of fossil resources from CO2 by utilizing solar energy is to achieve stable photocatalysts with effective CO2 adsorption capacity and high charge‐separation efficiency. A hierarchical direct Z‐scheme system consisting of urchin‐like hematite and carbon nitride provides an enhanced photocatalytic activity of reduction of CO2 to CO, yielding a CO evolution rate of 27.2 µmol g −1 h −1 without cocatalyst and sacrifice reagent, which is >2.2 times higher than that produced by g‐C3 N4 alone (10.3 µmol g −1 h −1 ). The enhanced photocatalytic activity of the Z‐scheme hybrid material can be ascribed to its unique characteristics to accelerate the reduction process, including: (i) 3D hierarchical structure of urchin‐like hematite and preferable basic sites which promotes the CO2 adsorption, and (ii) the unique Z‐scheme feature efficiently promotes the separation of the electron–hole pairs and enhances the reducibility of electrons in the conduction band of the g‐C3 N4 . The origin of such an obvious advantage of the hierarchical Z‐scheme is not only explained based on the experimental data but also investigated by modeling CO2 adsorption and CO adsorption on the three different atomic‐scale surfaces via density functional theory calculation. The study creates new opportunities for hierarchical hematite and other metal‐oxide‐based Z‐scheme system for solar fuel generation. Abstract : A hierarchical direct Z‐scheme hybrid for the photocatalytic reduction of CO2 without using any sacrifice agent or cocatalyst is developed by combining urchin‐like α‐Fe2 O3 and g‐C3 N4 . The coupling of the urchin‐like α‐Fe2 O3 with g‐C3 N4 can trigger significantly improved photoreduction activity of CO2 to form CO.